The law and the farmer - Kimball, Charles Augustus (My University, 1893)
Introduction: The history of the human race abounds in stories of oppression, caused by the existing state of society, towards the tillers of the soil. There is a feeling deep down in the hearts and minds of the masses, that for centuries, though the powers of government, the wealth producing classes have been misused. For years past, this feeling has pervaded the nation, and a constantly increasing murmur, especially from farmers, is arising against the upper classes, against other trades and professions, but most bitterly against the lawmakers and laws of the land as discriminating in favor of the wealthy and against the wealth producer. Many believe as a result of unjust laws, licensed fraud, and public corruption that the agricultural industry is so depressed that those who follow it can barely maintain a struggling existence and are rapidly approaching bitter ruin.
Citation: Kimball, Charles Augustus. The law and the farmer. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: History; Oppression; Government; Wealth; Unjust laws; Theses; Manuscripts (documents)